13+7х+12-9х=9

3х+5=2х+7

-6(2Х+1)= -42-3х

1,6(х-3)-0,6(2х-8) =0

Алекс117829 Алекс117829    1   30.03.2020 20:29    1

Ответы
yesenia2007 yesenia2007  12.10.2020 09:52

Пошаговое объяснение:

13+7х+12-9х=9

-2x + 25 = 9

2x = 25 - 9

2x = 16

x = 16 : 2

x = 8

3х+5=2х+7

3x - 2x = 7 - 5

x = 2

-6(2Х+1)= -42-3х

-12x - 6 = -42 - 3x

12x - 3x = 42 - 6

9x = 36

x = 36 : 9

x = 4

1,6(х-3)-0,6(2х-8) =0

1,6x - 4,8 - 1,2x + 4,8 = 0

0,4x = 0

x = 0

ПОКАЗАТЬ ОТВЕТЫ
danilka107 danilka107  12.10.2020 09:52

Відповідь:

Покрокове пояснення:

13+7х+12-9х=9

7х-9х=9-13-12

-2х= -16

х=8

зараз інші напишу

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика